Peningkatan Perilaku Hand Hygiene Enam Langkah untuk Pencegahan Penyakit Menular di Fasilitas Kesehatan - Niswatul Inayah; Syahda Fhauliah Putri, Anabela Sidik; Difa Razki, Nazwa Auliya Chaerunnisa; Mufidah Khoiriyyah, Alia Resti Andri Putri, Yunita Avita Ayu Nasution; Nawra Fazila, Azzahra Cinta Ramadhini (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Healthcare-Associated Infections (HAIs) remain a serious problem that requires immediate attention, due to low handwashing compliance. The World Health Organization (WHO, 2023) reports that hand hygiene compliance remains low, averaging only around 40% worldwide, and can be as low as 2% in low-income countries. In Indonesia, Ministry of Health data shows an incidence rate of 15.74%, while a survey of 10 teaching hospitals reported an average of 9.8%. Interventions in the form of hand hygiene education or training have proven effective in increasing knowledge and compliance among both patients and healthcare workers. In line with this, the community service activity was themed "Preventing Infectious Diseases and Infections with the Six-Step Handwashing Method." This activity was implemented as an educational effort to increase public and healthcare workers' awareness and skills in implementing proper hand hygiene practices in healthcare facilities. The activity began with coordination with the Cinere Community Health Center and was implemented through lectures and demonstrations of the WHO's six steps of handwashing using leaflets. A total of 30 participants took the pre-test and post-test to assess their knowledge improvement and satisfaction with the activity. PKM participants were predominantly aged 25–69 years and female, with the majority having elementary school education (66.7%). Knowledge before the activity was predominantly in the poor category (93.3%) and increased significantly after PKM to 83.3% in the good category (p-value = 0.000). The conclusion of this study is that the improvement of six-step hand hygiene behavior at the Cinere Community Health Center has successfully achieved the stated objective, namely increasing public knowledge about the importance of handwashing in preventing infectious diseases. The evaluation results showed a significant increase in participant knowledge from the poor to good category after education and demonstrations.